1-(tert-Butoxycarbonyl)piperidine-4-carboxylic acid - Hoong-Kun Fun; Suhana Arshad; Dinesh; S. Vivek; G. K. Nagaraja (Acta Crystallographica Section E, 2011)
In the title compound, C11H19NO4, the piperidine ring adopts a chair conformation. In the crystal, molecules are linked by intermolecular O—H...O and C—H...O hydrogen bonds, forming a layer parallel to the bc plane.